Classical Ethiopic: a grammar of Gǝʿǝz - Tropper, Josef (Languages of the Ancient Near East, 2021)
Frontmatter -- Contents -- Preface -- 1. Introduction -- 2. Writing and Orthography -- 3. Phonology -- 4. Morphology -- 5. Morphosyntax -- 6. Syntax -- Abbreviations and Bibliography -- Appendix A: Sample Texts in Original Script and Transliteration -- Appendix B: List of Signs -- Appendix C: Main Paradigms -- Appendix D: Glossary